2021
DOI: 10.20473/ijar.v3i22021.62-70
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Urine Syndecan-1 as A Predictor of Acute Kidney Injury In Pediatric Sepsis Patients

Abstract: Introduction: AKI (Acute Kidney Injury) complications in sepsis patients generally occur 24 hours after admission to ICU. Creatine Serum Concentration is a standard parameter to diagnose AKI. Unfortunately, the changes in creatine serum concentration will only be seen several days after the decrease of renal function to 50%.  The low detection ability has been linked with time loss before preventive therapy is commenced. Furthermore, this instigates the need for biomarkers to ensure early detection. Objective:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…28 Among pediatric septic patients after 48-72 hours of hospitalization at Dr. Soetomo General Academic Surabaya, the cut-off value of 1,242 ng/ml was found with a sensitivity of 76.5% and specificity of 61.5%. 19 Based on a case series report at Dr Soetomo General Academic Surabaya, it was found that although the clinical results were very good, the incidence of AKI after coronary artery bypass graft (CABG) surgery was relatively high. Most patients only experienced AKI for a short time and then recovered.…”
Section: Discussionmentioning
confidence: 99%
“…28 Among pediatric septic patients after 48-72 hours of hospitalization at Dr. Soetomo General Academic Surabaya, the cut-off value of 1,242 ng/ml was found with a sensitivity of 76.5% and specificity of 61.5%. 19 Based on a case series report at Dr Soetomo General Academic Surabaya, it was found that although the clinical results were very good, the incidence of AKI after coronary artery bypass graft (CABG) surgery was relatively high. Most patients only experienced AKI for a short time and then recovered.…”
Section: Discussionmentioning
confidence: 99%